Interdisciplinary care programme to improve self‐management for cancer patients undergoing stem cell transplantation: a prospective non‐randomised intervention study. (9th February 2016) - Schmidt, H.; Boese, S.; Bauer, A.; Landenberger, M.; Lau, A.; Stoll, O.; Schmoll, H.‐J.; Mauz‐Koerholz, C.; Kuss, O.; Jahn, P.
Abstract : The purpose of this single‐centre prospective non‐randomised study was to evaluate the effectiveness of an interdisciplinary care programme to enhance self‐management in patients with haematopoietic stem cell transplantation (HSCT). Patients undergoing HSCT, aged >14 years with informed consent were recruited ( n = 79). Patients in the intervention group (IG) received standard care plus the SCION‐HSCT intervention to counteract three problems after HSCT: muscle weakness, oral mucositis and malnutrition. Control group patients received standard care. Primary endpoint was global health‐related quality of life (HRQoL) at discharge (EORTC QLQ C30 v. 3.0). Baseline characteristics were balanced between both groups, except physical performance (ECOG) being significantly lower for patients of the IG. At discharge, no group differences could be seen regarding HRQoL. Non‐confirmatory post hoc analyses showed for patients of the IG a shorter duration of hospitalisation (MD −10.90; 95% CI −18.05 to −3.75) and increased activity during hospitalisation (MD 2.44; 95% CI 1.27–3.61). In conclusion, clinical effectiveness of the intervention could not be proven with respect to the aspired improvement of HRQoL. However, the nurse‐led interdisciplinary caring programme could be carried out in every day ward routine. Further research should focus on working mechanisms of complex interventions aiming to improve HRQoL of patients undergoing HSCT.